2019
DOI: 10.2147/cmar.s197349
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Immune inflammation indicators in anal cancer patients treated with concurrent chemoradiation: training and validation cohort with online calculator (ARC: Anal Cancer Response Classifier)</p>

Abstract: Background: In anal cancer, there are no markers nor other laboratory indexes that can predict prognosis and guide clinical practice for patients treated with concurrent chemoradiation. In this study, we retrospectively investigated the influence of immune inflammation indicators on treatment outcome of anal cancer patients undergoing concurrent chemoradiotherapy. Methods: All patients had a histologically proven diagnosis of squamous cell carcinoma of the anal canal/margin t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…Considering that recurrent inflammation episodes can promote the dysplasia-carcinoma sequence and a higher SII is a poor prognostic factor for response to treatment in SCC of the anus, defining high-risk patients for recurrence and individualizing treatment modalities are crucial for CA cases. 6,16 The strength of this study is its homogenous cohort of patients with CA with well-defined exclusion criteria, including autoimmune or other inflammatory disorders, which may have created a strong bias in terms of PIBs. The large sample size of the patients with CA, including those with recurrence and HSIL, is another superiority that renders the study unique in defining a stratification of CA patients according to risk groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering that recurrent inflammation episodes can promote the dysplasia-carcinoma sequence and a higher SII is a poor prognostic factor for response to treatment in SCC of the anus, defining high-risk patients for recurrence and individualizing treatment modalities are crucial for CA cases. 6,16 The strength of this study is its homogenous cohort of patients with CA with well-defined exclusion criteria, including autoimmune or other inflammatory disorders, which may have created a strong bias in terms of PIBs. The large sample size of the patients with CA, including those with recurrence and HSIL, is another superiority that renders the study unique in defining a stratification of CA patients according to risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 In addition, from a biological standpoint, anogenital lesions ranging from low-to high-grade SIL may be a precursor for malignant transformation to anal cancer considering that 80-90% of anal squamous cell carcinomas are associated with these SILs. 5,6 Recurrence and carcinogenesis contribute to the failure of treatment; therefore, combined surgical and immune modulator therapies in these selected cases may be more effective than expected. 3 The neutrophilto-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and systemic immune-inflammation index (SII) are peripheral inflammatory biomarkers (PIBs) that have been validated as markers of systemic inflammation and present prognostic values in several neoplasia, including anal cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few years, research interest has grown on the interplay between cancer, inflammation, and the immune system and several bio-humoral immune-based prognostic scores, such as Lymphocyte count, Neutrophil-Lymphocyte ratio (NLR), and Platelet-Lymphocyte ratio (PLR), have been identified as predictors of survival, recurrence, and treatment response in cancer patients [11][12][13]. In patients affected with anal cancer and treated with concurrent chemo-radiation (CT-RT), our group highlighted the prognostic value of the Systemic Index of Inflammation (SII) [14], low baseline Hb level [8], and high baseline eosinophil level [15] in predicting for poor response to CT-RT.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Several papers in the literature have reported that inf lammatory indexes such as neutrophil-tolymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR) and systemic inflammatory index (SII) may have a predictive and prognostic role in various diseases. [8][9][10][11][12][13][14][15] We previously demonstrated in two different papers a correlation between CRP 16 and inflammation index 17 and clinical outcome in patients with metastatic CC undergoing first-line chemotherapy.…”
Section: Introductionmentioning
confidence: 99%